2015
DOI: 10.1155/2015/358396
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine Attenuates Oxidative Stress Induced Lung Alveolar Epithelial Cell ApoptosisIn Vitro

Abstract: Background. Oxidative stress plays a pivotal role in the lung injuries of critical ill patients. This study investigates the protection conferred by α 2 adrenoceptor agonist dexmedetomidine (Dex) from lung alveolar epithelial cell injury induced by hydrogen peroxide (H2O2) and the underlying mechanisms. Methods. The lung alveolar epithelial cell line, A549, was cultured and then treated with 500 μM H2O2 with or without Dex (1 nM) or Dex in combination with atipamezole (10 nM), an antagonist of α 2 receptors. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…Previous studies showed that inflammatory mediators reduced E‐cad expression in the epithelium . Fujita et al .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous studies showed that inflammatory mediators reduced E‐cad expression in the epithelium . Fujita et al .…”
Section: Discussionmentioning
confidence: 95%
“…Recent studies have demonstrated a decrease in E‐cad expression in the gingival epithelium of gingivitis and periodontitis . In addition, it has been reported that some inflammatory mediators such as tumor necrosis factor‐α (TNF‐α) and ROS decrease E‐cad expression in human epithelial cells . However, whether there is a relationship between E‐cad expression and barrier function in human gingival epithelial cells stimulated with microbial toxic products has not been fully clarified yet.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therein, activated Bax can permeabilize the mitochondrial membrane, leading to the release of cytochrome c and subsequent cascade activations of caspases‐9, ‐3, and ‐6 [Ow et al, ]. In lung alveolar epithelial cells, Cui et al [] showed that dexmedetomidine could downregulate the Bax‐mediated signals and then attenuate hydrogen peroxide‐induced programmed cell death. In rats with intracerebral hemorrhage, dexmedetomidine was shown to alleviate impairment of short‐term and spatial learning memory by enhancing brain‐derived neurotrophic factor expression and suppressing apoptosis [Hwang et al, ].…”
mentioning
confidence: 99%
“…Oxidative stress is frequently cited to explain cell damage in various diseases. Cells have evolved an array of antioxidant defense systems to protect against the harmful effect of exogenous matters (Cui et al, 2015). Under oxidative condition, some antioxidants are tremendously synthesised to inhibit oxidation or reactions promoted by oxygen, peroxides, or free radicals or their actions.…”
Section: Introductionmentioning
confidence: 99%